2007
DOI: 10.1111/j.1540-8167.2007.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial Substrate Properties in Patients with Atrial Fibrillation

Abstract: The LA voltage was lower than the RA, and the atrial voltage correlated with the TAT. Electroanatomical remodeling of the atria could be crucial to the maintenance of AF. The LA substrate properties may play an important role in the recurrence of AF after catheter ablation of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 31 publications
3
84
0
Order By: Relevance
“…1,2 A large extent of the atrial arrhythmic substrate is associated with the limited efficacy of radiofrequency catheter ablation (RFCA) of AF. 3- 5 The size of the left atrium (LA) is related to structural remodeling and has been identified as an independent predictor of AF recurrence after RFCA. 6-8 The total atrial conduction time reflects not only structural but also electrical atrial remodeling.…”
Section: Study Populationmentioning
confidence: 99%
“…1,2 A large extent of the atrial arrhythmic substrate is associated with the limited efficacy of radiofrequency catheter ablation (RFCA) of AF. 3- 5 The size of the left atrium (LA) is related to structural remodeling and has been identified as an independent predictor of AF recurrence after RFCA. 6-8 The total atrial conduction time reflects not only structural but also electrical atrial remodeling.…”
Section: Study Populationmentioning
confidence: 99%
“…8, 9 In brief, each patient underwent an electrophysiological study and catheter ablation in a fasting, non-sedated state after written informed consent was obtained. After completing an intact right atrial (RA) and LA geometry reconstruction using the NavX mapping system, a sequential contact voltage map was constructed in all patients during sinus rhythm before the radiofrequency (RF) ablation.…”
Section: Electrophysiological Study and The Contact Electroanatomicalmentioning
confidence: 99%
“…Chang et al also demonstrated a worsening of the atrial voltage, as well as prolongation of the atrial activation time, as the AF progressed from paroxysmal to chronic. 13 There is a good correlation between the decrement in LA voltage and prolongation of the atrial activation time. Lo et al also found progressive remodeling of the atrial substrate in patients with recurrent AF (Figure 1).…”
Section: Providing a Guide For Atrial Substrate Modificationmentioning
confidence: 99%
“…14 Much evidence for identifying the substrate properties has been provided by both contact and noncontact mapping systems. [13][14][15][16][17][18][19][20][21][22] Using the contact mapping system, it was reported by Sanders et al that slowing of atrial regional conduction with a greater number of electrograms with fractionation and areas of low voltage occurred in patients with congestive heart failure and sinus node disease. 14, 16 Verma et al reported that the preexistence of a LA scar in patients undergoing PV isolation was a powerful, independent predictor of a procedural failure.…”
Section: Providing a Guide For Atrial Substrate Modificationmentioning
confidence: 99%
See 1 more Smart Citation